Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Kusumahadi Santosa Karanganyar - Sari, Putri Juwita, Drs. Ma'ruf, MM (2017)
This study aims to determine the effect of compensation and work motivation on employee performance of PT. Santosa Kusumahadi Karanganyar. This type of research is quantitative research. The samples in this study were employees of PT. Santosa Kusumahadi Karanganyar with questionnaires of 100 respondents, techniques in this study using simple random sampling. Data analysis methods used are validity, reliability, and test multiple linear regression analysis with t test, F test, and the coefficient of determination (R ²). Hypothesis tests showed the influence of compensation and motivation have a significant effect with t respectively 6,944 and 2,943. In the F test shows that jointly compensation and motivation variables significantly influence employee performance with a probability value of 0.000 (0.000 <0.05). And the coefficient of determination (R ²) equal to 47.5%.